ヤカン ノ デンリソウ キュウシュウ 2. キョウタイイキ ジュシンキ ニ ヨル ナンキョク カンソクセン ジョウ デンカイ キョウド ソクテイ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 若井, 登; ワカイ, ノボル; 藤井, 周; フジイ, シュウ; 宮本, 善行; ミヤモト, ヨシユキ; WAKAI, Noboru; FUJII, Shu; MIYAMOTO, Yoshiyuki (国立極地研究所, 1971)
P(論文) Narrow-band receivers developed for receiving exclusively the JJY signal in the presence of interferences by the other standard frequency waves with an identical carrier frequency are used since 1967 for the observation of HF radio wave absorption on board the ship of the Japanese Antarctic Research Expedition. This paper summarizes the technicality of the receiver, and presents the results of measurements obtained in the 10th JARE (Nov., 1968-Apr., 1969) by means of the receiver. Dependence of the ionospheric absorption in the nighttime on the solar activity was confirmed quantitatively by the same analysis as that given in Part I (1971) of this paper. departmental bulletin paper